The crosstalk among autophagy, apoptosis, and pyroptosis in cardiovascular disease - Cong, Lin; Bai, Yunpeng; Guo, Zhigang (Frontiers in Cardiovascular Medicine, 2022)
In recent years, the mechanism of cell death has become a hotspot in research on the pathogenesis and treatment of cardiovascular disease (CVD). Different cell death modes, including autophagy, apoptosis, and pyroptosis, are mosaic with each other and collaboratively regulate the process of CVD. This review summarizes the interaction and crosstalk of key pathways or proteins which play a critical role in the entire process of CVD and explores the specific mechanisms. Furthermore, this paper assesses the interrelationships among these three cell deaths and reviews how they regulate the pathogenesis of CVD. By understanding how these three cell death modes go together we can learn about the pathogenesis of CVD, which will enable us to identify new targets for preventing, controlling, and treating CVD. It will not only reduce mortality but also improve the quality of life.